PENGARUH AUDIT TENURE DAN REPUTASI KAP TERHADAP PENERBITAN OPINI GOING CONCERN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2009-2011) - Stevanus THJ; Abdul Rohman (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to examine the impact audit tenure and audit firm reputation on issued going concern while mandatory audit firm is going. Many factor can affect going concern opinion both positively and negatively. Previous studies on going concern opinion found different results, so it need to be repeated to verify previous research on going concern opinion.Samples were gathered from audit reports of 128 manufacturing companies that were liste in Indonesia Stock Exchange (IDX) during 2009-2011 reporting period. Research variables used were audit tenure, audit firm reputation, and going concern audit opinion. By using logisitic regression analysis with SPSS 20application, this study tried to examine the influence of audit tenure and audit firm reputation on issued going concern opinion.The results were as follows : (1) audit tenure does not significantly affect on issued going concern opinion, (2) audit firm reputation significantly affect on issued going concern opinion.